2022
DOI: 10.3389/fneur.2022.934501
|View full text |Cite
|
Sign up to set email alerts
|

Altered Intrinsic Brain Activity in Patients With Toothache Using the Percent Amplitude of a Fluctuation Method: A Resting-State fMRI Study

Abstract: ObjectiveThe percent amplitude of fluctuation (PerAF) technique was utilized to evaluate the neural functions of specific cerebrum areas in patients with toothache (TA).Patients and MethodsAn aggregation of 18 patients with TA (eight males and 10 females) were included in the study. We also recruited 18 healthy controls (HCs; eight men and 10 women) aligned for sex and age. Resting functional magnetic resonance imaging (rs-fMRI) scans were obtained. Then, we utilized the PerAF method and a support vector machi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 60 publications
0
1
0
Order By: Relevance
“…Studies have shown that TA increases ALFF in the left postcentral gyrus, right paracentral lobule, right lingual gyrus, right inferior occipital gyrus, left syrinx, and right superior occipital gyrus ( 15 ), and increases degree centrality (DC) values in the right lingual gyrus, right precentral gyrus, and left middle temporal gyrus ( 16 ). Yang et al ( 17 ) showed that the PerAF signal in the right dorsolateral superior frontal gyrus and right postcentral gyrus of patients with TA was lower than that in HC. The above studies provide a basis for neuroimaging to better understand the consciousness and cognitive changes associated with TA.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that TA increases ALFF in the left postcentral gyrus, right paracentral lobule, right lingual gyrus, right inferior occipital gyrus, left syrinx, and right superior occipital gyrus ( 15 ), and increases degree centrality (DC) values in the right lingual gyrus, right precentral gyrus, and left middle temporal gyrus ( 16 ). Yang et al ( 17 ) showed that the PerAF signal in the right dorsolateral superior frontal gyrus and right postcentral gyrus of patients with TA was lower than that in HC. The above studies provide a basis for neuroimaging to better understand the consciousness and cognitive changes associated with TA.…”
Section: Introductionmentioning
confidence: 99%